2013
DOI: 10.1134/s1063785013040214
|View full text |Cite
|
Sign up to set email alerts
|

Trivalent zirconium and hafnium ions in yttria-based transparent ceramics

Abstract: During the synthesis of ceramics based on Y 2 O 3 (yttria), it is common practice to use dioxides of tet ravalent ions (ThO 2 , ZrO 2 , HfO 2 ) as sintering addi tives, which simultaneously favor an increase in the transparency of ceramics. In particular, Yttralox-a ceramic material created by General Electric Co. (United States)-consists of 90 mol % Y 2 O 3 and 10 mol % ThO 2 and is close to glass with respect to transmission in the visible spectral range [1]. Russian specialists [2,3] have developed a techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In this situation, the control over the formation of oxygen vacancies and changes in their content, depending on the conditions of synthesis, becomes of particular importance. It was shown in [20] that this control can be performed indirectly by measuring the paramagnetic resonance spectra, which show the presence of trivalent hafnium and zirconium ions in Yb:Y 2 O 3 + 6HfO 2 and Yb:Y 2 O 3 + 6ZrO 2 . In the present paper, it is shown that the relative content of defective oxygen can be determined directly by measuring X-ray photoelectron O 1s spectra, which allows for choosing the most optimal annealing conditions to obtain the maximum optical transparency of ceramics.…”
mentioning
confidence: 99%
“…In this situation, the control over the formation of oxygen vacancies and changes in their content, depending on the conditions of synthesis, becomes of particular importance. It was shown in [20] that this control can be performed indirectly by measuring the paramagnetic resonance spectra, which show the presence of trivalent hafnium and zirconium ions in Yb:Y 2 O 3 + 6HfO 2 and Yb:Y 2 O 3 + 6ZrO 2 . In the present paper, it is shown that the relative content of defective oxygen can be determined directly by measuring X-ray photoelectron O 1s spectra, which allows for choosing the most optimal annealing conditions to obtain the maximum optical transparency of ceramics.…”
mentioning
confidence: 99%
“…It was identified that the photodarkening effect is caused by using the tetravalent Zr 4+ as the sintering additive. The charge imbalance between the Zr 4+ and Y 3+ induces the formation of ZrnormalY·${\rm{Zr}}_{\rm{Y}}^ \cdot $ point defects, which act as acceptors 20 . The electrons of the excited laser ions can be trapped by the Zr 4+ acceptors and decrease the laser oscillation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The charge imbalance between the Zr 4+ and Y 3+ induces the formation of Zr ⋅ Y point defects, which act as acceptors. 20 The electrons of the excited laser ions can be trapped by the Zr 4+ acceptors and decrease the laser oscillation efficiency. In the meantime, a Zr 4+ bound with an electron and forms a Zr 3+ color center, 25 which is responsible for the photodarkening observed on the laser ceramics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations